Exploitation of Algal-Bacterial Consortia in Combined Biohydrogen Generation and Wastewater Treatment - Shetty, Prateek; Boboescu, Iulian Z.; Pap, Bernadett; Wirth, Roland; Kovács, Kornél L.; Bíró, Tibor; Futó, Zoltán; White, Richard Allen; Maróti, Gergely (Frontiers in Energy Research, 2019)
Microalgae cultivation in municipal, industrial and agricultural wastewater is an emerging, highly effective approach for resource recovery and concomitant bioenergy generation. Wastewater effluents represent ideal sources of nutrients for eukaryotic green algal species. However, the performance of photosynthetic green algae is strongly dependent on the associated bacterial partners present in the effluents. Our combined wastewater treatment and biohydrogen evolution approach applied green microalgae-based photoheterotrophic degradation using dark fermentation wastewater effluent as substrate. The results showed that condition-dependent mutualistic relationships between the microbial and Chlorella algae populations had direct impact on the biodegradation efficiency and also on algal biohydrogen production. Metagenome analysis of the novel hybrid biodegradation system together with total nitrogen and phosphorous analytics provided important clues for the primary importance of the green algae partner in nitrogen and phosphorous removal. Bacterial bin genome data also indicated algal growth promotion by bacterial partners. With further development and optimization this new approach can lead to a highly efficient simultaneous organic waste mitigation and renewable energy production technology.